Rancang Bangun Mini Trainer Potensiometrik Sensor Sebagai Media Pembelajaran - Irma Yulia Basri; Agus Nasrianto; Andrizal Andrizal (Universitas Negeri Padang, 2022)
Learning media is a tool that can help the teaching and learning process that can clarify the meaning of information or messages to be conveyed, so as to achieve better learning objectives. This study aims to determine the performance, feasibility level of the trainer on the basic concept of potentiometric sensors as a learning medium. This study uses the Research and Development (R&D) method which consists of analysis, design, product manufacture, testing and implementation. The data collection was carried out 3 times in the testing phase. The data obtained will be processed in several stages, namely the Accuracy test, Linearity Test and Repeatibility Test as well as a feasibility test from media experts and respondents. The average results of the research that have been carried out obtained an average accuracy of 99.14%, Linearity Test data has Linearity, Repeatibility Test obtained 0. Judging from the feasibility level test from Media Experts, namely 93.74% and Respondents 94.78%. so it can be concluded after doing some testing that the basic concept trainer of the potensiometric sensor as a learning medium can be said to be “very feasible” to be used as a learning medium